2021
DOI: 10.1016/j.jtho.2021.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Accuracy and Comprehensiveness of Pathology Reports for Resected NSCLC in a High Mortality Area of the United States

Abstract: Introduction: Complete and accurate pathology reports are vital to postoperative prognostication and management. We evaluated the impact of three interventions across a diverse group of hospitals on pathology reports of postresection NSCLC.Methods: We evaluated pathology reports for patients who underwent curative-intent surgical resection for NSCLC, at 11 institutions within four contiguous Dartmouth Hospital Referral Regions in Arkansas, Mississippi, and Tennessee from 2004 to 2020, for completeness and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These results showed that, in NSCLC, miR-328-5p is a novel tumor suppressor by targeting LOXL4. With a high incidence and poor survival rates, NSCLC has been the leading cause of cancer-associated mortality worldwide (1,2,17). NSCLC can be divided into 2 major categories, namely squamous cell carcinoma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed that, in NSCLC, miR-328-5p is a novel tumor suppressor by targeting LOXL4. With a high incidence and poor survival rates, NSCLC has been the leading cause of cancer-associated mortality worldwide (1,2,17). NSCLC can be divided into 2 major categories, namely squamous cell carcinoma and adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is 1 of the most common malignancies worldwide, with high morbidity and mortality. 1 Non-small cell lung cancer (NSCLC) is accountable for more than 80% of lung cancer cases. 2 In the past decades, due to the neglect of health and the constraints of economic and technical conditions, most of lung cancer were found to be in the middle and advanced stage, and the treatment prognosis was poor.…”
Section: Introductionmentioning
confidence: 99%